Um estudo da interação mãe-bebe segundo uma visão psicanalítica: a interferência dos canais sensoriais na construção das relações objetais - Goldenberg, Gita Wladimirski (1986)
The results achieved l e d us to have a larger understanding not only of the subject s we studied but also of the most important methodological rules which should guide clinical researches such as this one. Keeping up with the works published in the two latest de cades - such as those written by T. B. Brazelton, Klaus,kennel, C. Bertrand , M. Soulé - the results of our research corroborate the evidence of the baby 's active participation in the process of interaction with mother since his birth. We could also verify the high de gree of mutuality and deriving exchanges which produce the inconscious dialogue between the another and her new born baby. Finally our investigation showed that, above any kind of deficiency in the channels or in the material means of communication, it is language which organizes and build up the human being’s personality.